NZ J Ecol 2018
DOI: 10.20417/nzjecol.42.33
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the understory in 132 woody weed populations and implications for succession

Abstract: The species composition of the understory can be a key indicator of successional trajectories in the absence of disturbance at forested sites. We surveyed species composition and percent cover in the understory of 132 closed-canopy stands of 41 woody weed species throughout New Zealand as a first step in understanding potential successional trajectories in these weed populations. Twenty-seven weed species had zero, or very few, conspecific seedlings or saplings present beneath their own canopy. Fourteen weed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…However, there may be reasons other than shade-intolerance that explain why a species does not regenerate under its own canopy. In New Zealand for example, the shade-tolerant woody weed species sycamore (Acer pseudoplatanus) and tree privet (Ligustrum lucidum) regenerate under their own canopy at some sites, but not at others (McAlpine et al 2018). A potential explanation for this variability in regeneration across sites is that interspecific competition varies across one or more resource gradients (D'Antonio & Chambers 2006).…”
Section: Scenario a Understory Is Predominantly Nativementioning
confidence: 99%
See 2 more Smart Citations
“…However, there may be reasons other than shade-intolerance that explain why a species does not regenerate under its own canopy. In New Zealand for example, the shade-tolerant woody weed species sycamore (Acer pseudoplatanus) and tree privet (Ligustrum lucidum) regenerate under their own canopy at some sites, but not at others (McAlpine et al 2018). A potential explanation for this variability in regeneration across sites is that interspecific competition varies across one or more resource gradients (D'Antonio & Chambers 2006).…”
Section: Scenario a Understory Is Predominantly Nativementioning
confidence: 99%
“…However, as we are not concerned with predicting the persistence of individual native species, there only needs to be a mix of seedlings and saplings of native species as a group (rather than seedlings and saplings of each species). In a survey of 132 woody weed stands around New Zealand, McAlpine et al (2018) recorded as many as 24 native species in the understory at some sites, and 55 sites had ten or more native species in the understory (KGM unpubl. data).…”
Section: Scenario B Canopy Weed and Natives Are Abundant In The Undementioning
confidence: 99%
See 1 more Smart Citation
“…Although there were few mature rainforest trees growing among the privet regrowth, a larger number (although still modest, and limited by cattle grazing) were present as seedlings, especially of bird‐dispersed species. Conversely, McAlpine et al () reviewed several cases of low native seedling recruitment in privet stands and concluded that privet was not a useful regeneration facilitator.…”
Section: Australian Case Studiesmentioning
confidence: 99%
“…Management decisions could then draw on an evidence‐based understanding of their ecological roles, and better information about whether these roles are environmentally harmful or useful (see, e.g. McAlpine et al ()).…”
Section: Conservation Dilemmas and Future Directionsmentioning
confidence: 99%